THE USE OF THE INTERNET APPLICATIONS IN INCREASING STUDENTS’ LITERACY IN ENGLISH - Tlewkabulova Aynura (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. The article theoretically justifies the use of the internet and mobile applications in language learning in industry. A model for students' development of internet resource use in practice has been created. Methodological support has been provided for the process of developing students' competence to utilize internet sites in industry practice. The criteria, indicators, and levels of success of the process for developing students' internet resource competence in industry practice have been determined. A trial study has been conducted and the efficacy of the suggested model for developing students' resource use competence has been verified.